A utilização de um aplicativo para registro das informações de pacientes de odontologia sob a ótica do cirurgião-dentista - Tavares, Aglae Regina Pessoa Giansanti (2016)
The Dental Record collects all necessary documentation so that the dental surgeon can adequately perform his work, as well as its importance in eventual judicial demands and cases of human identification. Once it is a complex document, not all dental surgeons dare to carry out the correct recording and filing of this information. On the other hand, there is a number of apps on market directed to the health area for several purposes, among them professional support is highlighted. Therefore, the objective of this research was to show how the dental-surgeons perceived the technology of the mobile devices (smartphones or tablets) and how it would aid in their work routine by analyzing an application for the registry of information of patients Because it was still an unexplored topic, 10 dentists, using a semi-structured questionnaire, conducted an in-depth interview, with the objective of understanding how this type of technology could contribute, taking into account its possibilities and current limits. It was, therefore, a qualitative, exploratory and descriptive research; and they analyzed responses using the Content Analysis technique. The results showed that according to the view of dentists, this technology could be useful in archiving and storing information. The conclusion was that 90% of the dental-surgeons interviewed said that the application helps in clinical practice and 10% consider this technology still limited to this function.